A Survey on Reading Strategies Implemented by the English Study Program Students of FKIP Universitas Riau - Kurnia, Anita; Novitri, Novitri; Syarfi, M. (FKIP - Universitas Riau, 2025)
This study investigated the types of reading strategies applied by 5th semester students of the English Department at Riau University. The background of this study emphasizes how important good reading techniques are for academic achievement as students often do not know how to improve their comprehension. Knowing the types and frequency of reading strategies used by the students was the main objective of this study. A total of 99 students from three classes were given questionnaires to complete as part of the descriptive-quantitative technique. With a focus on comprehension monitoring and summarizing tactics, the results showed a variety of reading strategies, including cognitive, metacognitive, and social strategies. The results show that skilled readers use a wide variety of useful techniques, which improve reading comprehension and general academic achievement. This research helps create efficient teaching strategies and provides prospective teachers with the knowledge they need to improve reading comprehension skills. Ultimately, the study underscores the importance of fostering strategic reading among students to support their learning journey.